Effect of the cultivation site on the percentage of flowers set and the weight and size of fruits of the two apple varieties Golden delicious and Starking delicious - قره علي كرم; جرجس مخول; عبد العزيز بوعيسى (Latakia University Journal -Biological Sciences Series, 2024)
The study was conducted during the year 2022 in Latakia Governorate in Slanfa, Kassab, and Khirbet Solas, with the aim of studying the effect of altitude above sea level on the flowering and some characteristics of the fruits of the Golden delicious and Starking delicious apple varieties. It was observed that there was a clear effect of the geographical location and the cultivated variety on flowering indicators and some specifications of the apple fruits studied. The results of the statistical analysis also showed that the Slenfeh site was superior to the Kassab and Khirbet Solas sites in terms of setting percentage. The highest contract rate was recorded for the Golden Delicious variety at the Slenfeh site (51.9%), then the Kassab site (41.5%), and then the Khirbet Solas site (37.3%). The Kassab site also outperformed the Khirbet Solas site, and the same also applies to the Starking delicious variety. The contract percentage reached 41.9, 24.4, and 17.1%, respectively. The highest value for the percentage of remaining fruits was recorded for the Starking Delicious cultivar (68.73, 58.07, 43.58%) in Khirbet Solas, Kassab, and Slanfeh, respectively. While the Golden Delicious cultivar reached (58.5, 44.78, 40.09%) for Khirbet Solas, Kassab, and Slanfah sites, respectively. The results of the statistical analysis showed the superiority of the Khirbet Solas site compared to the other two sites. The largest value for both the average weight and size of the fruit was recorded for the Starking Delicious variety (160.2 g, 166.3 cm3), significantly superior to the Golden Delicious variety (103.6 g, 112.5 cm3). Keywords: Apple, Golden Delicious, Starking Delicious, setting percentage, fruit weight, fruit volume, site height.